Reviewing and Evaluating the Feminine Mystique: An Effective Book in the Formation of Feminism Second Wave - Fatemeh Ghasempour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Friedan’s book is one of the most important feminist works in importance and impact, as well as the Waltoncroft Women’s Rights and the Second Gender of Simon de Beauvoir. This book, an attempt to identify the “anonymous problem” as Friedan describes it, has had a significant impact on the formation of the second wave of feminism. In this book, Friedan examines the causative factors and consequences of the “anonymous problem” and then presents his solution to this problem. The factors causing this problem are both influenced by existing scientific theories and the dominant discourse of American society in the fifth decade of the 20th century. Friedan states that women under the semantic system of that time had perceived femininity as the most important factor in their identity and had been able to perform family roles with all vigor, but the important issue was that they were not satisfied with the situation and that this problem was not satisfying for them. In fact, this book seeks to invite women into the public sphere and enjoy the same social benefits as men. The book’s evaluation shows that the author of this work seeks to create a metaphor for solving women’s problems without this being an all-encompassing issue and focusing on urban middle-class women, providing a strategy for all women.